Effect of weed control, fertilizer application and Rhizobium - on nutrient uptake under maize + soybean intercropping system - R. L. JAT,; B. L. GAUR, (Indian Journal of Agronomy, 2001)
A field experiment was conducted during rainy season (kharif) 1993 and 1994 on clay-loam soils of Rajasthan College of Agriculture, Udaipur. Maximum NPK uptake by maize and soybean was recorded under manual weeding twice, followed by application of metolachlor and pendimethalin 1.0 kglha. Among weed-control treatments, unweeded check recorded the highest NPK uptake by the weeds. Fertilizer levels and Rhizobium inoculation to intercrop had no effect on nutrient uptake of maize, but significantly increased the nutrient uptake of soybean.
Keywords: .Weed control; Maize-soybean intercropping; Rhizobium; Nutrient uptake